2003
DOI: 10.2754/avb200372030359
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Lymphocyte Subpopulations in Immune Organs of Chickens Infected with Salmonella enteritidis

Abstract: To determine the effect of different doses of Salmonella enteritidis on immunocompetent cells, the thymus, bursa of Fabricius, and peripheral blood were examined. One-day-old chickens were orally infected with 2 × 10 2 CFU/ml (low dose) and 2 × 10 8 CFU/ml (high dose) of S. enteritidis PT4. Subsets of T lymphocytes (CD3, CD4, and CD8), and BU1b cells using an indirect immunofluorescent method and flow cytometry were analysed on days 7, 10, 14, 21, and 27 postinoculation (dpi). The actual number of lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
9
1
3
Order By: Relevance
“…In contrary to this Asheg et al, (2003) reported that in White Plymouth Rock chicken the Bu1b+ cell count was highest in four week-old birds and lowest in two week-old birds. CD3+ cell count was highest in two week-old birds and lowest in seven day-old birds.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…In contrary to this Asheg et al, (2003) reported that in White Plymouth Rock chicken the Bu1b+ cell count was highest in four week-old birds and lowest in two week-old birds. CD3+ cell count was highest in two week-old birds and lowest in seven day-old birds.…”
Section: Resultscontrasting
confidence: 86%
“…As age advances, Bu-1a+ cell count also increased up to four week of age and thereafter there was a decline in the cell count. Statistically, the results showed significant difference between day-old, two week and four week-old birds but there was no significant difference in Bu-1a+ cell count between four week and six week-old birds as reported by Asheg et al, (2003) in White Plymouth Rock chicken. In all the age groups studied, Bu-1a+ cell count was more than CD3+, CD4+ and CD8+ cell count indicative of the major cell population in the bursa are B lymphocytes than CD3+, CD4+ and CD8+ T cells.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…There is an increased proliferation of B-lymphocytes 21 days after contact with the antigen [19], which may explain the increased levels of this cell population after immunization with the live vaccine. CD28 + T cells are T lymphocytes that have not yet undergone terminal differentiation, being still capable of replication in response to stimulus.…”
Section: Live Vaccinementioning
confidence: 99%
“…Também, foi demonstrada redução no número de células CD4 + e CD8 + no sangue periférico de galinhas infectadas com Sallmonella Enteritidis em comparação com o grupo controle não-infectado. Neste caso, sugere-se que esse fenômeno está relacionado à migração destas células para o sitio de ação da infecção, com redução de sua expressão no sangue (Asheg et al 2003). Em aves vacinadas e submetidas à infecção com Salmonella Enteritidis, foi observado aumento da quantidade de células citotóxicas no ceco indicando saída de células da circulação com destino ao tecido desaϐiado (Berndt et al 2006).…”
Section: Experimentounclassified